(untitled) (Journal of Informatics Education and Research, 2025)
It is beyond doubt that women make important contributions to agricultural and rural economies across all regions of the world, despite differing viewpoints. To enable the rural women farmers to overcome or manage their farm management concerns, public policy support is being extended by the government, however much needs to be done as yet in this regard for the same. An effort has been made through this research to uncover the aspect of leveraging policy measures to enhance the participation of rural women in farm management and land operation practices. Post this, the influence of participation and productivity enhancement on the economic well-being of women is analyzed. A total of 2000 women farmers as per a scientifically designed sample plan were approached for interviews of which 1010 were completed. The present study has made an effort to describe the same from the perspective of participation in various activities, frequency of participation, classification as per the pre-harvest and post-harvest activities, the constraints encountered in the process, etc. It is found that ‘type’ of activity revealed that the majority of women were involved in Seeding followed by Land clearing, planting, and harvesting. The strategic aspect of “Marketing” is taken up by a very meagre number, thereby indicating that rural women still need inclusion in policy aspects and that of decision-making aspects to ensure that their role is elevated. The data on ‘decision making’ however revealed that women were indeed having a certain sense of liberty to take impactful decisions affecting their farm-related prospects.